2016
DOI: 10.1039/c6ra15531f
|View full text |Cite
|
Sign up to set email alerts
|

Improved dispersibility of nano-graphene oxide by amphiphilic polymer coatings for biomedical applications

Abstract: The poor dispersibility of graphene-based nano-materials in aqueous media is a crucial limitation in their biological applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…To overcome these obstacles, numerous types of biological or synthetic polymers, such as hyaluronic acid derivatives, dextran, heparin, polyethylene glycol (PEG), phospholipid-polyethylene glycol, polystyrene- co -poly­(acrylic acid), and polystyrene- co -poly 4-vinylpyridin, have been utilized for coating rGO nanosheets. Although, all these surface molecules increase the stability of rGO in aqueous media they are not optimized for targeted delivery to tumor cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these obstacles, numerous types of biological or synthetic polymers, such as hyaluronic acid derivatives, dextran, heparin, polyethylene glycol (PEG), phospholipid-polyethylene glycol, polystyrene- co -poly­(acrylic acid), and polystyrene- co -poly 4-vinylpyridin, have been utilized for coating rGO nanosheets. Although, all these surface molecules increase the stability of rGO in aqueous media they are not optimized for targeted delivery to tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…21,27 Despite the promising properties of rGO for photothermal therapy applications, the use of rGO has been limited by low stability in aqueous media due to the absence of surface hydrophilic groups. 28−32 To overcome these obstacles, numerous types of biological or synthetic polymers, 33 such as hyaluronic acid derivatives, 34 dextran, 22 heparin, 35 polyethylene glycol (PEG), 36 phospholipid-polyethylene glycol, 37 polystyrene-co-poly(acrylic acid), 37 and polystyrene-co-poly 4-vinylpyridin, 37 have been utilized for coating rGO nanosheets. Although, all these surface molecules increase the stability of rGO in aqueous media they are not optimized for targeted delivery to tumor cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Imani et al also found changes in size of the rGOs when surface polymers were added, in addition, a small drop in zeta potential was also observed when PEG was added. 33 …”
Section: Resultsmentioning
confidence: 99%
“…Imani et al also found changes in size of the rGOs when surface polymers were added, in addition, a small drop in zeta potential was also observed when PEG was added. 33 The PEGFA was obtained by 3 synthetic routes. The products of all steps were characterized by 1H NMR and FTIR and the precursor PEG for comparison.…”
mentioning
confidence: 99%
“…Octylbenzene is a type of alkylbenzene; however, in their research, other molecules were not investigated. It has been under the argument that the alkyl chain [23][24][25][26][27] or aromatic moiety [28][29][30][31][32][33][34][35][36] contributes to the graphene dispersion. To make clear the role of the alkyl chain and the aromatic moiety of the dispersant, we synthesized a series of alkylbenzenes and evaluated their graphene dispersing abilities.…”
Section: Introductionmentioning
confidence: 99%